2006
DOI: 10.1158/1541-7786.mcr-05-0141
|View full text |Cite
|
Sign up to set email alerts
|

Adaptor Molecule Crk Is Required for Sustained Phosphorylation of Grb2-Associated Binder 1 and Hepatocyte Growth Factor–Induced Cell Motility of Human Synovial Sarcoma Cell Lines

Abstract: Activation of the c-Met receptor tyrosine kinase through its ligand, hepatocyte growth factor (HGF), promotes mitogenic, motogenic, and morphogenic cellular responses. Aberrant HGF/c-Met signaling has been strongly implicated in tumor cell invasion and metastasis. Both HGF and its receptor c-Met have been shown to be overexpressed in human synovial sarcoma, which often metastasizes to the lung; however, little is known about HGF-mediated biological effects in this sarcoma. Here, we provide evidence that Crk ad… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 61 publications
4
66
0
Order By: Relevance
“…CRK silencing remarkably suppresses tumour formation in human synovial sarcoma cell xenografts and invasive growth in vivo 91,92 . In glioblastoma cells, CRK over-expression increases cell migration and invasion, likely through an association with DOCK180 26 and its silencing suppresses early attachment to laminin, cell motility and growth 27 .…”
Section: Migration and Invasionmentioning
confidence: 99%
“…CRK silencing remarkably suppresses tumour formation in human synovial sarcoma cell xenografts and invasive growth in vivo 91,92 . In glioblastoma cells, CRK over-expression increases cell migration and invasion, likely through an association with DOCK180 26 and its silencing suppresses early attachment to laminin, cell motility and growth 27 .…”
Section: Migration and Invasionmentioning
confidence: 99%
“…Overexpression of Crk and CrkL has been reported in several human cancers, including oral squamous cell carcinoma (5), ovarian carcinoma (6), colon cancer (7), lung cancer (8,9), breast cancer (10,11), gastric cancer (12), and glioblastoma (13,14). Reduced expression of either Crk or CrkL by RNA interference-mediated knockdown lowered the in vivo tumor formation of human ovarian (15), synovial sarcoma (16), glioblastoma (14), breast cancer (10), head and neck squamous cell carcinoma (17), and rhabdomyosarcoma (18) cell lines. Taken together, these reports imply that elevated levels of Crk family proteins promote cell transformation and enhance tumor cell growth (for review see Refs.…”
mentioning
confidence: 99%
“…This is important because certain crucial therapeutically vulnerable elements of a pathway may lie upstream or downstream to the primary molecular aberration, precluding its identification in expression/mutation-based analyses. Several studies have suggested involvement of the architecture-regulating ephrin pathway and signaling pathways such as Wnt, IGF, ERBB2, HGF/MET, and b-catenin in synovial sarcoma [2,4,47,62,78,82,84]. New studies continue to provide further insight into how such pathways are involved in certain facets of the tumor phenotype.…”
Section: Molecular Abnormalitiesmentioning
confidence: 99%